Investigating the Impact of Work Motivation and Leadership Styles on Employee Performance in the Production Department - Mughni, Fauzan Dhanie; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to investigate the influence of work motivation and leadership style on employee performance in the Production Department of PT Unicharm Indonesia. The research employs a quantitative approach with descriptive and verification methods. The study population consists of all employees within the Production Department of PT Unicharm Indonesia. Data analysis was conducted using SPSS software to test the research hypotheses. The findings indicate that work motivation significantly affects employee performance on a partial basis. Similarly, leadership style also shows a significant partial influence on employee performance. Furthermore, both motivation and leadership style together have a significant simultaneous impact on employee performance. These results underscore the critical role of effective work motivation and leadership style in enhancing employee performance within the organization.